ANALISIS DAMPAK MENONTON DRAMA KOREA TERHADAP PESERTA DIDIK KELAS VIII MTS N 2 PONTIANAK - Alimudin, Muhammad; Yuline, Yuline; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to descibe about the impact of watching korean dramas in students. The method used is descriptive method and the form of research used is survey research. The population in this study were students who watched korean drama class VIII amounting to 70 students. This study a quantitative approach. Data collection techniques indirect communication techniques while the data collection tools were questionnaires. result of this study indicated that the impact of watching korean drama is in the ?Quite High? category. The impact of watching korean drama positively with the highest percentage is increasing language knowledge 78%, entertainment facilities 76%, recognizing the life culture in the country of korea 76%, and moral message 76%, obtained overall result 76% with ?High? category. The negative impact of watching korean drama with the highest percentage was too forgetting the time 72%, less socializing 72%, too dramatic 72% and leaving real activity 70%, the overall number was 70% in the ?Quite High? category. the impact of watching korean dramas on class VIII students as a whole obtained a 75% result in the ?Quite High? category. the impact of watching korean drama on students of class VIII is quite high. Keywords: Analysis, The Impact Of Watching Korean Drama.